Hellenistic inter-state political ethics and the emergence of the Jewish state - Mendels, Doron (Jewish and Christian texts in contexts and related studies, 2021)
"Doron Mendels demonstrates how inter-state political ethics gave rise to the emergence of the Jewish state during the years 200-168 BCE and provides an overview of how these values functioned"